New Techniques in Systems Neuroscience - Douglass, Adam D. (Biological and Medical Physics, Biomedical Engineering, 2015)
This volume is essential reading for anyone wishing to understand the recent explosion of experimental tools in neuroscience that now make it possible to manipulate, record, and understand neuronal activity within the intact brain, and which are helping us to learn how the many neurons that comprise a network act together to control behavior. Leaders in the field discuss the latest developments in optogenetics, functional imaging, circuit mapping, and the application of these tools to complex biological problems. New Techniques in Systems Neuroscience Explores cutting-edge methodological developments and their biological motivations Covers state-of-the-art advances in optogenetics, imaging, circuit mapping, and the molecular characterization of individual neurons Describes key examples of how these methods have been applied in different model organisms Is appropriate for experts and those just entering the field alike.